IRAN AND AFGHANISTAN SOFT POWER DIPLOMACY - Niaz Mohammad Hamdard; Abdulbasit Elham; Rafiudeein Shahid (Policy Research Journal, 2025)
This study explores the evolving soft power dynamics between Iran and Afghanistan after 2021, focusing on how Iran has utilized various strategies to influence Afghan society. Before the Taliban's return to power, Iran had successfully leveraged its anti-imperialist rhetoric, media outreach, educational institutions, and charity organizations to build a strong soft power presence in Afghanistan. Iran's advocacy for regional solidarity, particularly its vocal stance on Palestine and anti-Western activism, resonated with many Afghans, strengthening its image as a champion of resistance against imperialism. The study investigates how these tools have fared under the Taliban regime, which has implemented restrictive policies, particularly on media, education, and foreign influence. Through primary data gathered from journalists, experts, and international relations scholars, the study reveals that Iran’s soft power has diminished under the Taliban. The regime’s crackdown on media freedom, the closure of educational institutions, and its restrictive approach to NGOs and foreign organizations have curtailed Iran’s ability to engage with Afghan society in the same way it did during the previous government. Despite these challenges, Iran has managed to maintain some influence by emphasizing its anti-imperialist stance and promoting regional connectivity through initiatives like the Chabahar port. However, the internal policies of both the Taliban and Iran, such as border tensions, have contributed to the erosion of Iran’s previously strong soft power in Afghanistan, leaving it struggling to maintain the same level of influence in the region.